NICE - Neutron Induced Charged particle Emission. (October 2020) - Al-Khasawneh, K.; Borris, E.; Bruückner, B.; Eberhardt, K.; Erbacher, P.; Fiebiger, S.; Gernhäauser, R.; Göobel, K.; Heftrich, T.; Kisselbach, T.; Kurtulgil, D.; Langer, C.; et al.
Abstract: A new detector setup (NICE-detector) based on an organic plastic scintillator is presented. It will be used during experiments measuring neutron-induced reactions with a charged particle in the exit channel. The proposed design was tested at the Goethe University Frankfurt. One of the test cases was the capture cross-section of 209 Bi at different astrophysically important energies, including thermal capture cross-section and resonance integral. This research presents the performance of the detector setup, as well as preliminary results for the calculated cross-sections. The preliminary results demonstrate that the newly developed NICE-detector can be used to determine capture cross-sections with sufficient accuracy, and might be adopted in the future as an alternative for charged particle measurements in different nuclear and astrophysical applications.